PENDEKATAN SEKURITISASI TERHADAP KRISIS PENGUNGSI MYANMAR: ANTARA KEAMANAN WILAYAH DAN TANGGUNG JAWAB KEMANUSIAAN THAILAND - Ramadhani, Riva (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
The Myanmar refugee crisis triggered by political conflict and violence in Myanmar has created major challenges for Thailand, especially in maintaining a balance between border security and humanitarian obligations. This research analyses how the Myanmar refugee crisis affects security dynamics on the Thai-Myanmar border as well as the strategies implemented by Thailand to manage border security while considering refugee protection. Using a desk study approach, this research integrates various academic sources to understand the complexity of this issue. The findings show that Thailand tends to prioritise national security through a securitisation approach, which often limits refugees' access to protection and humanitarian assistance. However, pressure from the international community and humanitarian organisations is pushing Thailand to adopt a more balanced approach. This research contributes to the study of forced migration, regional security, and ASEAN policy by highlighting the dilemma between state sovereignty and humanitarian responsibility.